2005
DOI: 10.1128/jcm.43.7.3519-3521.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak of Pediatric Gastroenteritis Caused by CTX-M-14-Type Extended-Spectrum β-Lactamase-Producing Strains of Salmonella enterica Serovar London

Abstract: CTX-M-14-type extended-spectrum ␤-lactamase was first detected in Salmonella enterica serovar London strains which were isolated from three hospitalized pediatric patients with gastroenteritis. The isolates had pulsed-field gel electrophoresis patterns identical to those of the previously isolated antimicrobialsusceptible strains from community-acquired gastroenteritis, suggesting the susceptible clone acquired the resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…In Korea, a few isolates of TEM-52, CTX-M-14, and CTX-M-15 ESBL-producing Salmonella spp. were detected, of which CTX-M-15 was the most common, followed by CTX-M-14 (13,19,29,30). In the present study, 7 CTX-M-producing Salmonella isolates were identified.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In Korea, a few isolates of TEM-52, CTX-M-14, and CTX-M-15 ESBL-producing Salmonella spp. were detected, of which CTX-M-15 was the most common, followed by CTX-M-14 (13,19,29,30). In the present study, 7 CTX-M-producing Salmonella isolates were identified.…”
Section: Discussionmentioning
confidence: 47%
“…All the Salmonella isolates were examined for the presence of bla CTX-M by PCR and direct sequencing using 4 primer sets (Table 1) (18,19). The PCR reaction was performed under the following conditions: 949 C for 5 min, followed by 35 cycles of 949 C for 30 s, 609 C for 30 s, and 729 C for 30 s, with a final extension at 729 C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…ESBL phenotypes were positive only in strain E5026 and its transconjugant, and PABL activity was detected in all isolates ( Table 2). The presence of known MBLs (bla VIM , bla IMP , bla SPM-1 , bla GIM-1 , bla AIM-1 , bla SIM-1 , and bla NDM-1 ) (13, 24), ESBLs (bla TEM , bla SHV , and bla CTX-M ) (25), and PABL genes (17) were determined using PCR. We also aimed to detect ISAba125 and 16S rRNA methylase (armA) by using the published primers (7).…”
mentioning
confidence: 99%
“…A few isolates of TEM-25 and CTX-M-14 ESBL-producing Salmonella spp. have been reported in Korea [11,12]; however, prior to the present case, there had been no reports of ESBL production in S. enterica serotype Enteritidis.…”
Section: Discussionmentioning
confidence: 53%